Quality of low‐carbohydrate diets among Australian post‐partum women: Cross‐sectional analysis of a national population‐based cohort study - Sophie Lewandowski; Elizabeth Neale; Ellie D'Arcy; Allison M. Hodge; Danielle A. J. M. Schoenaker (Wiley, 2023)
Abstract Low‐carbohydrate diets (LCDs) are popular among people attempting weight loss and recommended for pregnant women with gestational diabetes (GDM), but they may increase health risks if nutritionally inadequate. We aimed to describe the dietary intake of post‐partum women according to their relative carbohydrate intake, overall, and among women attempting weight loss or diagnosed with GDM in their recent pregnancy. This cross‐sectional population‐based cohort study included 2093 post‐partum women aged 25-36 years who participated in the Australian Longitudinal Study on Women's Health. Dietary intake was assessed using a validated food frequency questionnaire. Relative carbohydrate intake was determined using a previously developed LCD score. Data were weighted to account for oversampling of women from rural/remote areas. More than half of women (n[weighted] = 1362, 66.3%) were trying to lose weight, and 4.6% (n[weighted]=88) had GDM in their recent pregnancy. Women with the lowest relative carbohydrate intake (LCD score quartile 4) consumed 36.8% of total energy intake from carbohydrates, and had a lower intake of refined grains, whole grains, fruit and fruit juice, and a higher intake of red and processed meat, compared with women with the highest relative carbohydrate intake (quartile 1). Different food groups, both healthy and unhealthy, were restricted depending on whether women were attempting weight loss and had recent GDM. These findings may reflect a lack of knowledge among post‐partum women on carbohydrates and dietary guidelines. Health professionals may have an important role in providing advice and support for post‐partum women who wish to restrict their carbohydrate intake, to ensure optimal diet quality.